1999
DOI: 10.1103/physrevc.59.607
|View full text |Cite
|
Sign up to set email alerts
|

Radiative capture of protons by deuterons

Abstract: The differential cross section for radiative capture of protons by deuterons is calculated using different realistic NN interactions. We compare our results with the available experimental data below Ex = 20 MeV. Excellent agreement is found when taking into account meson exchange currents, dipole and quadrupole contributions, and the full initial state interaction. There is only a small difference between the magnitudes of the cross sections for the different potentials considered. The angular distributions, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Moreover, in many cases the measured differential cross sections for p-d capture (aside from a normalization factor) can be explained theoretically over a large energy range. In [44] it was already shown that a similar normalization problem exists for the data below E x = 20 MeV. There, it was also shown that the angular distribution is insensitive to the underlying two-body interaction, whereas there is a strong correlation between the three-body binding energy and the normalization constant A 0 [42,43].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, in many cases the measured differential cross sections for p-d capture (aside from a normalization factor) can be explained theoretically over a large energy range. In [44] it was already shown that a similar normalization problem exists for the data below E x = 20 MeV. There, it was also shown that the angular distribution is insensitive to the underlying two-body interaction, whereas there is a strong correlation between the three-body binding energy and the normalization constant A 0 [42,43].…”
Section: Discussionmentioning
confidence: 86%
“…In Refs. [42][43][44], we have treated the 3 He and 3 H photodisintegration and the inverse processes, i.e., the radiative capture of protons or neutrons by deuterons, within the integral equation approach discussed below. These calculations were based on the Bonn A, Bonn B and Paris potentials in Ernst-Shakin-Thaler (EST) expansion: Bonn A (EST), Bonn B (EST), and Paris (EST) [45,46].…”
mentioning
confidence: 99%
“…The only difference is that the driving term of the n-d scattering equation ( i.e., the particle-exchange diagram, the so-called "Z" diagram) is replaced by the off-shell extension of the plane-wave pion-absorption amplitude. More details can be found in [15,31] and references therein.…”
Section: Theorymentioning
confidence: 99%
“…For further applications of separable approximations or expansions, e.g., in processes as the photodisintegration of three-nucleon systems [15,16], the corresponding radiative capture [17], or the pion absorption on such systems [18], additional tests of accuracy of the threebody wave functions involved appear desirable. In case of a 5 channel calculation and the EST method such a test has been made already in Ref.…”
Section: Introductionmentioning
confidence: 99%